2020
DOI: 10.1111/agec.12563
|View full text |Cite
|
Sign up to set email alerts
|

Are pesticides risk decreasing? The relevance of pesticide indicator choice in empirical analysis

Abstract: The reduction of adverse health and environmental effects from pesticide use is currently a top priority on the agricultural policy agenda. Efficient pesticide policies must take into account farmers' application behavior, especially effects of pesticide use on economic risk. However, previous results regarding the direction of risk effects of pesticides are ambiguous. We show that the ambiguity in earlier studies could be due to the pesticide indicator selected. Indicators which fail to account for the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 76 publications
(105 reference statements)
1
37
0
Order By: Relevance
“…As discussed earlier the assumption of pesticides being risk decreasing applies only to some situations and there exists empirical evidence of pesticides being risk increasing or having no effect on risk (Möhring et al 2020). As said earlier we believe this assumption is not a major caveat of our study since the magnitude of the impact of risk aversion on input use is expected to be similar (but of the opposite direction) if pesticides were risk increasing instead.…”
Section: Robustness To the Assumptions On Technology And Risk Preferementioning
confidence: 72%
See 2 more Smart Citations
“…As discussed earlier the assumption of pesticides being risk decreasing applies only to some situations and there exists empirical evidence of pesticides being risk increasing or having no effect on risk (Möhring et al 2020). As said earlier we believe this assumption is not a major caveat of our study since the magnitude of the impact of risk aversion on input use is expected to be similar (but of the opposite direction) if pesticides were risk increasing instead.…”
Section: Robustness To the Assumptions On Technology And Risk Preferementioning
confidence: 72%
“…Moreover in our framework, pesticide use is measured with pesticide expenditure, which is a simplification. When available, information on both quantity and quality of pesticides should be considered since the risk properties of pesticides depend not only on the quantity used but also on their toxicity (Möhring, Gaba and Finger 2019;Möhring et al 2020).…”
Section: Robustness To the Assumptions On Technology And Risk Preferementioning
confidence: 99%
See 1 more Smart Citation
“…Pest development and weather conditions are processes with major stochasticity, leading to uncertainties in crop growth and efficiency of pesticides 34 . Risk perception and preferences of farmers -and information about uncertainties -influence their evaluation of pest management costs and gains so that they may not follow a strictly profit maximizing rationale 35 . Further, behavioral factors, such as perception biases and habits influence the farmers' decisionmaking 36,37 .…”
Section: Farmer and Consumer Actionsmentioning
confidence: 99%
“…Previous research showed that pest development, as well as weather conditions are processes with major underlying stochasticity, leading to uncertainties with regard to crop growth and efficiency of pesticides 10,11 . Studies have repeatedly shown that these uncertainties play an important role for farmers' pesticide application behaviour [12][13][14][15][16] . Further, such uncertainties potentially play an important role for farmers' rationale for pesticide timing -with large implications for agricultural pesticide use levels.…”
Section: Introductionmentioning
confidence: 99%